2015
DOI: 10.1089/neu.2014.3456
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Malondialdehyde Levels and Mortality in Patients with Severe Brain Trauma Injury

Abstract: There is a hyperoxidative state in patients with trauma brain injury (TBI). Malondialdehyde (MDA) is an end-product formed during oxidative stress, concretely lipid peroxidation. In small studies (highest sample size 50 patients), higher levels of MDA have been found in nonsurviving than surviving patients with TBI. An association between serum MDA levels and mortality in patients with TBI, however, has not been reported. Thus, the objective of this prospective, observational, multicenter study, performed in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 23 publications
9
47
0
Order By: Relevance
“…AIH and rAIH elicit motor plasticity in non-respiratory motor systems following spinal injury (Lovett-Barr et al, 2012; Trumbower et al, 2012; Hayes et al, 2014; Prosser-Loose et al, 2015), and we demonstrated previously increased growth/trophic factor expression associated with dAIH-induced motor plasticity in both respiratory (C 4 ) and non-respiratory (C 7 ) motor nuclei (Lovett-Barr et al, 2012). We now demonstrate similar changes in key growth/trophic factors at other CNS sites associated with non-respiratory motor behaviors, including the motor cortex and non-respiratory (C 7 and L 3 ) spinal motor neurons.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…AIH and rAIH elicit motor plasticity in non-respiratory motor systems following spinal injury (Lovett-Barr et al, 2012; Trumbower et al, 2012; Hayes et al, 2014; Prosser-Loose et al, 2015), and we demonstrated previously increased growth/trophic factor expression associated with dAIH-induced motor plasticity in both respiratory (C 4 ) and non-respiratory (C 7 ) motor nuclei (Lovett-Barr et al, 2012). We now demonstrate similar changes in key growth/trophic factors at other CNS sites associated with non-respiratory motor behaviors, including the motor cortex and non-respiratory (C 7 and L 3 ) spinal motor neurons.…”
Section: Discussionmentioning
confidence: 54%
“…For example, a single presentation of AIH elicits transient increases in sympathetic nerve activity (Dick et al, 2007; Xing and Pilowsky, 2010) and daily AIH (dAIH) for one week elicits prolonged improvement in forelimb function of rats with cervical spinal injuries, an effect that lasts weeks following treatment (Lovett-Barr et al, 2012; Prosser-Loose et al, 2015). A single AIH exposure (15, 1-min hypoxic episodes, 9% inspired O 2 ; 1-min intervals) improves leg strength in persons with chronic spinal injuries (Trumbower et al, 2012), and dAIH (15, 1.5 min episodes per day, 9% O 2 ; 1.5 min intervals) and dAIH paired with 30-min of overground walking practice improved walking speed and endurance in patients with chronic incomplete spinal cord injuries (Hayes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They actively regulate macrophages, 17,18 neutrophils, 19,20 dendritic cells, 21-23 and natural killer cells, 24,25 thereby modulating the first line of defense. MSCs also regulate the adaptive immune system, i.e., B and T lymphocytes.…”
Section: Immunosuppressive Properties Of Mesenchymal Stem Cellsmentioning
confidence: 99%
“…In the multiple logistic regression analysis was found an association between serum MDA levels >2.27 nmol/mL and 30-day mortality (Odds Ratio = 7.23; 95% CI =1.84-28.73; p = 0.005) controlling for GCS and age. We found in the survival analysis that patients with serum MDA higher than 2.27 nmol/mL presented higher mortality at 30 days than patients with lower levels (Hazard ratio = 2.9; 95% CI = 1.31-6.33; p = 0.005).Also in other clinical circumstances, such as patients with sepsis [85,86] and brain trauma injury [87] has been found an association between circulating MDA levels and patient mortality.I think that those higher circulating levels of MDA in patients with MMCAI than in controls and in non-survivors patients than in surviving, represents a higher lipid peroxidation in non-survivors patients.In several clinical trials, ischemic stroke patients were randomized to the administration of different antioxidant vitamins (B2, B6, B12, C, E) or not [88][89][90] …”
mentioning
confidence: 59%
“…Also in other clinical circumstances, such as patients with sepsis [85,86] and brain trauma injury [87] has been found an association between circulating MDA levels and patient mortality.…”
Section: Malondialdehydementioning
confidence: 96%